Water quality of streams and wells of north Perlis: a comparative analysis - Wan Ruslan Ismail,; Haslina Sarju,; Mashhor Mansor, (Environmental Management Society, Malaysia, 2007)
Water resources in catchment area came from various sources. Water from the surface infiltrate and leached down to the ground water. Land use activities on the surface will affect water quality of both surface and underground water. Underground water has been use by Malaysian as their water resources. Perlis and Kelantan are the two states in Malaysia that have a lot of wells still in use for water supply especially during dry season. This study investigates the spatial and temporal changes in water quality of surface and ground water of north Perlis from July 2001-December 2001. Results indicate that generally well water had lower physico-chemical values and nutrient content compared to stream water. A significant difference was observed for DO, pH, SRP and turbidity. The higher concentrations of calcium in wells reflecting the influence of geology on water quality. Nutrient contamination is minimal and the most probable source of water pollution is from agricultural runoff, fertilizers and domestic waste causing the water quality of north Perlis to degrade